Development of Interactive Digital Student Worksheets for IPAS Learning on Plant Parts for Fourth Grade Elementary School Students - Nopi Nopa Sari; Sri Sumarni; Cecil Hiltrimartin (Jurnal Penelitian Pendidikan IPA, 2026)
This study aims to develop and evaluate a digital Student Worksheet (LKPD) for IPAS learning on the topic of plant parts for fourth-grade elementary school students. The research employed a Research and Development (R&D) approach, which included the stages of needs analysis, design, development, and product testing. Expert validation was conducted by subject-matter experts, media experts, and language experts to assess the feasibility of the content, visual design, language use, and usability of the digital LKPD. Practicality testing was carried out through one-to-one evaluation and small group testing, while effectiveness was analyzed by comparing pretest and posttest scores and calculating students’ N-gain values. The results indicate that the digital LKPD demonstrates a high level of validity and practicality, with the content, media, and language aspects categorized as very valid, and good ease of use and acceptability observed in the practicality tests. Analysis of learning outcomes shows an increase in students’ average scores from pretest to posttest, with the average N-gain falling into the high category, indicating that the digital LKPD supports students’ conceptual understanding of plant parts. This study concludes that the use of digital LKPD can serve as an alternative interactive learning medium that promotes active student engagement; however, further testing on other subject matter and with larger samples is needed to strengthen these findings.